Analisis Peluang dan Tantangan Bagi Indonesia dalam Kerjasama Ekonomi Digital dengan Arab Saudi Tahun 2019 - Permata Sari, Shania Indah; Priadarsini, Ni Wayan Rainy; Kawitri Resen, Putu Titah (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2021)
Indonesia is one of the countries that is focusing on developing its digital economy potencies. Currently, Indonesia is the country with the largest internet economy in Southeast Asia due to the intense digital business development that has been carried out since 2016. In addition, Indonesia is also supported by quite capable digital potential. The initiative to collaborate with Saudi Arabia through digital economic cooperation agreements also opens up more opportunities for Indonesia as Asia's Digital Energy in 2020. However, the impact of the development of the digital economy also brings its own challenges that must be faced by the Indonesian government and also for the Indonesian people. This scientific research aims to analyze the opportunities and challenges for Indonesia in the digital economic cooperation with Saudi Arabia in 2019 by using qualitative explanatory method. Keywords : Indonesia, Saudi Arabia, Digital Economy, Opportunities and Challenges